The Story of a Broken Sofa: Adult Education Meets Activist Art to Envision the Future of Adult Education - Cynthia Stevens; Gabriele Strohschen (Adult Education Research Conference, 2022)
This AERC Symposium addressed envisioning an Adult Education structure that meets societal needs. Within an activist art project paradigm, old and new adult education theories and practices informed the discussion.
Keywords: 21st Century Education; Metagogy; Activist Art; CbLP; Service Learning; PLA